Improvement in symptoms of psoriasis in a child after treatment with grass pollen specific allergen immunotherapy. - Sogut, A.; Yilmaz, O.; Yuksel, H. (European Journal of Pediatric Dermatology, 2007)
Psoriasis is a chronic inflammatory disease of skin in which Th1 lymphocytes have a central role. Similar to all inflammatory diseases, additional inflammation may lead to the exacerbation of manifestations. Allergic asthma is the chronic eosinophilic inflammatory disease of the bronchial mucosa in which Th2 lymphocyte activity predominates. A nine year old boy who had been under conventional topical treatment for psoriasis without improvement for three months, presented to the outpatient department with recurrent cough, dyspnea and wheezing of one year duration. The physical examination revealed white plaques on extensor surfaces of elbows and knees as well as prolonged expirium and wheezing. Positive allergen skin prick test against "olea europea" and "fraxinus excelsior" pollens were observed. Inhaled steroids and allergen specific immunotherapy were initiated with the diagnosis of allergic asthma. Psoriatic findings regressed without requirement for an additional topical treatment during follow up along with asthma findings. As a conclusion, inflammatory stress of allergic asthma may aggravate psoriasis and treatment with allergen specific immunotherapy may help decrease findings of psoriasis.